A Case using Wire Fixation for Mandible Fractures: A Simple and Cost-Effective Technique - Ni Nyoman Sintya Agniswari Anasta Putri; Agus Roy Rusly Hariantana Hamid (The International Journal of Medical Science and Health Research, 2025)
Background: Mandibular fractures are among the most common facial injuries, often caused by traffic accidents, physical violence, or sports-related trauma. These fractures frequently involve the symphysis and condylar process of the mandible, structures essential for masticatory function and jaw articulation. Immediate and appropriate management is crucial to prevent long-term functional impairment. Case: A 43-year-old female presented to emergency department following a traffic accident with complaints of severe jaw pain, particularly when moving or opening the mouth. CT scan confirmed a mandibular symphysis fracture and bilateral dislocated mandibular condylar process fractures. Intervention and Management: Intervention included wire fixation of the mandibular symphysis, arch bar placement on both the maxilla and mandible, And rubber arch bar for additional stabilization. Discussion: This Intervention and management have demonstrated efficacy in ensuring jaw stability. Wire fixation is often chosen as a simple and cost-effective alternative. However, complications such as infection, TMJ dysfunction, and malocclusion may arise if postoperative recovery is suboptimal. Conclusion: Wire fixation remains a viable treatment modality for mandibular fractures, particularly in settings with technological or financial constraints. Appropriate technique selection and postoperative care are critical to achieving optimal functional outcomes.